Analysis and design of a playout buffer for VBR streaming video - Steyaert, B.; Laevens, K.; De Vleeschauwer, D.; Bruneel, H. (Annals of operations research, 2008)
A critical component in the delivery of VBR streaming video over packet-based networks, is the playout buffer at the receiver side. As packets will incur a variable delay within the network, a mechanism is needed to dejitter the stream and assure that packets are played out at exactly the same rate at which they were generated by the sender. Packet loss at the playout buffer can be induced by either underflow or overflow, and we first identify the general conditions under which these events occur. These general rules require some knowledge on the network delay characteristics of an arbitrary packet, and are then further developed and refined, by taking a closer look at the case where a single delay bottleneck exists within the network. This analysis allows us to derive useful design rules, where we consider two cases, depending on whether or not the receiver has knowledge about the delay the first packet of the stream has incurred. We conclude by demonstrating that the traditional playout paradigm can be enhanced to guard against large initial delays.